Student Perceptions of Scientific Journals for Sports Science Students in 2022 - Muhammad Syahri; Rizka Syafrina; Tuan Anggi; Novita Novita; Nurkadri Nurkadri (JUMORA: Jurnal Moderasi Olahraga, 2023)
Critical thinking skills are developed by validating various information to develop new knowledge systematically in higher education practice activities that collect information, manage and make conclusions to verify the correctness of information, using various methods that make it possible to verify the correctness of information scientifically. In this era of digitalization, research is a much-needed part of society. Because research can provide education to the community in particular. Scientific writing is a paper that in the process includes the ability to think deeply about known concepts to produce new knowledge and understanding. The purpose of this study is to find out how much the level of understanding of students in the perspective of the world of writing scientific papers. Where the sample in this study is Sports science students from the UNIMED Faculty of Sports took part in this research. In this study the samples were taken using the aggregate sampling technique a total of 397 from the class of 2016, 2017, 2018, 2019, 2020, 2021 and 2022. In the instrument using questionnaires that will be distributed to samples to obtain valid data. which in the instrument found a validity value of 0.664 and reliability of 0.159. The result of this study is that as many as 82.1% of students understand about research articles and 17.9% do not know what research articles are. So from these results it can be concluded that the level of student understanding in research articles is included in the category of quite good. Of course, this needs to be given maximum education so that students fully understand the importance of the world of research.Keywords: Descriptive, journal, sport, student perspective